Persepsi Umat Islam Jember dalam Memutuskan Memilih Bank Syariah: Perceptions of the Muslim Community in Jember in Deciding to Choose an Islamic Bank - Mahmudah Mahmudah (Fenomena, 2007)
The low market share of Islamic banks in Jember Regency, despite its Muslim-majority population, highlights a gap between market potential and actualization. This study examines Muslim perceptions of Islamic banks' operational principles, products, and services, and how these perceptions influence the decision to choose Islamic banks. A descriptive-correlational design was used, with 100 respondents from three sub-districts selected through stratified random sampling. Multiple linear regression analysis showed that perceptions of operational principles and products and services significantly influence the decision to choose Islamic banks (F-count 36.43 > F-table 2.35; significance 0.000). The R Square value of 42.9% indicates that these two variables explain nearly half of the variation in the decision. It is concluded that intensifying literacy and promotion of Islamic banking, especially regarding products and services, is necessary to strengthen market share in Muslim-dominant regions. Fenomena rendahnya pangsa pasar bank syariah di Kabupaten Jember, meskipun didominasi Muslim, mengindikasikan adanya kesenjangan antara potensi pasar dan realisasi. Penelitian ini bertujuan mengkaji persepsi umat Islam terhadap prinsip operasional serta produk dan jasa bank syariah, serta pengaruhnya terhadap keputusan memilih bank syariah. Metode deskriptif korelasional diterapkan dengan sampel 100 responden dari tiga kecamatan (Kaliwates, Patrang, Sumbersari) melalui stratified random sampling. Analisis regresi linier berganda menunjukkan bahwa persepsi terhadap prinsip operasional dan produk/jasa secara simultan berpengaruh signifikan terhadap keputusan memilih bank syariah (F hitung 36,43 > F tabel 2,35; signifikansi 0,000). Nilai R Square 42,9% mengindikasikan kedua variabel tersebut menjelaskan hampir setengah dari variasi keputusan. Disimpulkan bahwa peningkatan literasi dan promosi bank syariah perlu diintensifkan, terutama pada aspek produk dan jasa, guna memperkuat pangsa pasar di wilayah dengan mayoritas Muslim.